Respuesta :

Answer:

Step-by-step explanation:

f(x) = x³ + 2x²  - 7x - 8

g(x) = -4x - 7

h(x) = 4x² - x - 15

k(x) = -x² + 7x + 4

a) h(x) - k(x) = 4x² - x - 15 - [-x² + 7x + 4]

                   = 4x² - x - 15 + x² - 7x - 4

                   = 4x² + x²   - x - 7x   - 15 - 4

                    = 5x² - 8x  - 19

b) f(x) - h(x) = x³ + 2x²  - 7x - 8 -[ 4x² - x - 15 ]

                   = x³ + 2x²  - 7x - 8 - 4x²  + x  + 15

                   = x³ + 2x² - 4x²  -7x + x  -8 + 15

                   = x³  - 2x²  - 6x + 7

c) f(x) - g(x) = x³ + 2x²  - 7x - 8 - [ -4x - 7 ]

                  =x³ + 2x²  - 7x - 8 + 4x + 7

                 = x³ + 2x²  - 7x + 4x   - 8 + 7

                 = x³ + 2x²  - 3x - 1

d) k(x) - f(x) =   -x² + 7x + 4  - [ x³ + 2x²  - 7x - 8]

                    = -x²  + 7x + 4 - x³ - 2x² + 7x + 8

                    =  -x²  -2x² + 7x  + 7x  + 4 + 8  - x³

                      = -3x²  + 14x + 12 - x³

                      = -x³  - 3x² + 14x +  12

ACCESS MORE